2021
DOI: 10.1556/2060.2021.00170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of malnutrition and body composition on the quality of life of COPD patients

Abstract: BackgroundPathological alterations in nutritional status may develop in Chronic Obstructive Pulmonary Disease (COPD) patients through production of inflammatory cytokines and inadequate diet.ObjectiveThe aim of our study was to determine the correlation between nutritional status and quality of life of COPD patients.MethodsWe evaluated the nutritional status of COPD patients of Hungarian National Koranyi Institute for Pulmonology using the Malnutrition Universal Screening Tool (MUST) and bioelectrical impedanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…FFMI, an indirect measure of muscle mass, is frequently used to define a condition in which there is abnormally low muscle mass together with impaired muscle strength or function, [71][72][73] and FFMI is also a reliable indicator of COPD mortality. 74,75 Patients with COPD who have abnormally low FFMI have detrimental effects on their ability to exercise, dyspnea, respiratory muscle function, and lung function. They also have a higher chance of dying and longer exacerbations.…”
Section: Ffmimentioning
confidence: 99%
See 1 more Smart Citation
“…FFMI, an indirect measure of muscle mass, is frequently used to define a condition in which there is abnormally low muscle mass together with impaired muscle strength or function, [71][72][73] and FFMI is also a reliable indicator of COPD mortality. 74,75 Patients with COPD who have abnormally low FFMI have detrimental effects on their ability to exercise, dyspnea, respiratory muscle function, and lung function. They also have a higher chance of dying and longer exacerbations.…”
Section: Ffmimentioning
confidence: 99%
“… Jamie R Chua et al 73 2019 Cross-sectional study Philippines Demographic, BMI, health information, body composition, grip strength, six-minute walking distance, FEV1, FEV1/FVC, PIF, PEF, CAT Sarcopenic COPD patients had statistically significant reduced peak inspiratory flow (r= −0.6074, P value 0.0001), peak expiratory flow (r= −0.3993, P value 0.0144), hand grip strength (r= −0.3751, P value 0.0007), and CAT score (r= −0.3751, P value 0.0157) compared to non-sarcopenic patients.ow FFMI had statistically significant reduction in PIF (r= −0.5791, P value 0.0002), PEF (r= −0.4475, P value 0.0055), and hand grip strength (r= −0.4560, P value 0.0027), however low CAT score (r= −0.3422, P value 0.0285). M. FEKETE et al 75 2021 Cross-sectional study Hungary Weight, BMI, FFM, Malnutrition Universal Screening Tool (MUST), body mass, body fat percentage, muscle percentage, water content, 6MWD, Spirometry, quality of life, the Saint George’s Respiratory Questionnaire (SGRQ-C), mMRC, CAT Respiratory distress was more frequent in patients with low FFMI compared to those with normal FFMI (FEV1ref%: 38.9 versus 48.6, P 5 0.023), FFMI was significantly correlated with FEV1 (r 5 0.370, P < 0.001) and 6MWD as well (r 5 0.531, P <0.001), as shown in Table 6 . We found a statistically significant relationship between CAT points and FFMI (r=5 0.4906, P 5=0.0003) and CAT points with SMMI (r=5 0.4532, P 5=0.0009).…”
Section: Introductionmentioning
confidence: 99%
“…With the aim of a multimodal approach to the disease and for a better understanding of the mechanisms underlying nutritional impairment, it is necessary to enrich the already florid literature on this topic. Future studies are needed to provide more information on the role of nutritional status in combination with aging and levels of daily activity in disease progression with the aim of assuring a better quality of life for COPD patients [ 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…COPD is not only a disease characterized by chronic, progressive loss of respiratory function and respiratory and systemic inflammation; it can also affect the entire body, leading to weight loss in approximately 20–50% of cases, which can become pathological [ 3 , 12 ]. Correcting malnutrition is an important part of maintenance therapy for COPD, and has been shown to improve exercise tolerance, quality of life, and survival in patients [ 6 , 13 , 14 , 15 ]. Numerous studies have revealed the benefits of a diet rich in antioxidants in COPD, including vitamins A, C, and E, beta-carotene, and micronutrients such as magnesium, selenium, and zinc [ 14 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Correcting malnutrition is an important part of maintenance therapy for COPD, and has been shown to improve exercise tolerance, quality of life, and survival in patients [ 6 , 13 , 14 , 15 ]. Numerous studies have revealed the benefits of a diet rich in antioxidants in COPD, including vitamins A, C, and E, beta-carotene, and micronutrients such as magnesium, selenium, and zinc [ 14 , 16 , 17 , 18 ]. In addition, the quality of the diet and the intake of long-chain polyunsaturated fatty acids (PUFAs; omega-3), which can reduce inflammation in many ways, are very important factors for chronically ill patients [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%